Fredric Wertham and the critique of mass culture - Beaty, Bart (University Press of Mississippi, 2005)
Too often remembered solely as the psychiatrist and cultural critic whose testimony in Senate subcommittees sparked the creation of the Comics Code, Fredric Wertham was a far more complex man. Author Bart Beaty traces the evolution of Wertham's attitudes toward popular culture and reassesses his place in the debate about pop culture's effects on youth and society. When The Seduction of the Innocent was published in 1954, Wertham (1895-1981) became instantly known as an authority on child psychology. Although he had published several books before Seduction, its sharp criticism of popular cultur.